Reliability and validity of malay version of revised oswestry low back pain disability questionnaire/ Zarina Zahari, Nor Azizah Ishak & Maria Justine - Zahari, Zarina; Ishak, Nor Azizah; Justine, Maria (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
The purpose of this study was to describe the process used to translate the Malay version of the ODQ and to test The Malay version in terms of test-retest reliability and validity among Malay low back pain (LBP) volunteers. The questionnaire was translated and back-translated following WHO recommendation. The Malay version was tested for 60 patients with low back pain. Test-retest with a two-day interval was performed. Internal consistency was assessed by Cronbach's alpha. Construct validity was assessed with correlation between the ODQ and the SF-36. Test-retest with a two-day interval was performed. Internal consistency and reliability of the Malay version of the ODQ was assessed by Cronbach's alpha and reached 0.821. Intraclass correlation coefficient was 0.821. Test-retest correlation reliability was 0.803. The ODQ was inversely correlated with the physical functioning scale of SF-36 and with mental scales of the SF-36. The reliability and construct validity of the Malay version of the Oswestry Disability Questionnaire were acceptable for assessing functional status of Malay speaking patients with low back pain.